Knowledge on COVID-19 and practice towards prevention of covid-19 among undergraduate students in Health Campus Universiti Sains Malaysia - Canti, Nurul Atikah Nuraini (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
COVID-19 is an infectious disease caused by a newly discovered coronavirus and causes many effects such as increased risk of mortality especially for elderly and financial constraint for health care system. A cross-sectional study has been conducted to determine students’ knowledge on COVID-19 and practice towards prevention of COVID-19 in Health Campus USM. This study also examined the relationship between knowledge on COVID-19 and practice towards prevention of COVID-19 among undergraduate students in Health Campus USM. Fisher Exact Test was used to determine the relationship between knowledge on COVID-19 and practice towards prevention of COVID-19. A total of 273 undergraduate students, 128 students were from the School of Medical Science, 56 students from the School of Dental Science and, 97 students from the School of Health Science were recruited through stratified sampling. Data were collected from November 2020 until June 2021 using google form and analyzed using SPSS version 26.0 for a window. Most of the respondents are female students (78.4%). The results revealed undergraduate students in Health Campus USM were having a high knowledge level (